2015
DOI: 10.1039/c5ra05266a
|View full text |Cite
|
Sign up to set email alerts
|

Application of ordered mesoporous silica nanocontainers in an anticorrosive epoxy coating on a magnesium alloy surface

Abstract: Epoxy coatings containing inhibitor loaded silica nanocontainers were applied to Mg alloy. When damage was caused in coatings during immersion time, the coatings displayed self-healing property with the release of inhibitor from nanocontainers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…The loading of healing agents inside small diameters are getting much attention these days. Porous or tubular forms of inorganic particles such as mesoporous silica [20,21], TiO 2 nanotube [22], hollow TiO 2 spheres [23], hollow porous Mn 2 O 3 microsphere [24] etc. are used as reservoirs for corrosion inhibitors or healing agents.…”
Section: Introductionmentioning
confidence: 99%
“…The loading of healing agents inside small diameters are getting much attention these days. Porous or tubular forms of inorganic particles such as mesoporous silica [20,21], TiO 2 nanotube [22], hollow TiO 2 spheres [23], hollow porous Mn 2 O 3 microsphere [24] etc. are used as reservoirs for corrosion inhibitors or healing agents.…”
Section: Introductionmentioning
confidence: 99%
“…This facilitated prolonged self-healing for long time in corrosive media. Epoxy coatings containing corrosion inhibitor (MBT) loaded mesoporous silica was proved to have selfhealing properties [81]. It was showed that epoxy coating with 4 wt% MBT loaded mesoporous silica had partial recovery from artificially created defects as shown by it response to EIS analysis when exposed to 3.5 wt% NaCl solution.…”
Section: Inorganic Nanomaterials As Self-healing Agent Containersmentioning
confidence: 99%
“…The longest diffusion distance from their carriers is also critically influence the self-healing Figure 9. Electrochemical impedance spectroscopy bode plots of epoxy-4 wt% silica-MBT coating after artificial defect exposure to 0.1 mol·L -1 NaCl solution [81] process in the two-part system. With a shorter diffusion distance at higher concentrations and efficient mixing lead to an improved healing performance.…”
Section: Combination Of Containers For Self-healing Epoxy Composites mentioning
confidence: 99%
“…Different types of micro- or nano-containers are used for the storage and release of corrosion inhibitors or self-healing agents, depending on if the specific corrosion triggering conditions are dependent upon chemical changes (e.g., on pH change) or upon mechanical damage6. Corrosion inhibitors or healing agents are usually immobilized or encapsulated inside polymeric micro capsules78910 and inorganic meso- and nano-porous materials2111213.…”
mentioning
confidence: 99%
“…Additionally, the use of inorganic nanomaterials as reservoirs for healing agents can eliminate the tedious encapsulation process. Previously, inorganic particles such as cerium molybdate15, mesoporous silica1316, hollow titanium dioxide spheres2, cerium titanium oxide17, etc., were reported as containers for corrosion inhibitors to provide self-healing protective coatings for metals. Fibrous and tube shaped materials including cellulose nanofibers1819, clay nanotubes202122, etc., have also been reported as effective containers for corrosion inhibitors.…”
mentioning
confidence: 99%